2023
DOI: 10.1101/2023.07.08.548221
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Conserved and repetitive motifs in an intrinsically disordered protein drive α-carboxysome assembly

Abstract: All photosynthetic bacteria and some chemoautotrophic bacteria fix CO2into sugars in specialized proteinaceous compartments called carboxysomes. Carboxysomes enclose the enzymes Rubisco and carbonic anhydrase inside a layer of shell proteins to increase the CO2concentration for efficient carbon fixation by Rubisco. In the α-carboxysome lineage, a disordered and highly repetitive protein named CsoS2 is essential for carboxysome formation and function. Without it, the bacteria are unable to fix enough carbon to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…In a recent study of the MR, we observed significant effects of the conserved tyrosine on the biochemical interactions with the shell and sufficiency of resulting carboxysomes for atmospheric growth in H. neapolitanus, highlighting a distinct yet crucial role of the M-peptides . The AlphaFold predictions for the C-peptides are of low confidence and lack a common structure.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…In a recent study of the MR, we observed significant effects of the conserved tyrosine on the biochemical interactions with the shell and sufficiency of resulting carboxysomes for atmospheric growth in H. neapolitanus, highlighting a distinct yet crucial role of the M-peptides . The AlphaFold predictions for the C-peptides are of low confidence and lack a common structure.…”
Section: Discussionmentioning
confidence: 90%
“…It is now well established that the CTD forms interactions with the carboxysome shell via both the C-peptides and CTP. , Our recent study found that the MR also specifically interacts with the shell hexamers and that the VTG triplets are an essential component of that interaction . To further test this interaction in the context of carboxysome assembly, we designed a series of MR-GFP fusion proteins having different numbers of M-peptides.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To successfully assemble a functional carboxysome in plants, it is necessary to have a comprehensive understanding of both the carboxysome lumen and the shell, and how these two components interconnect. The supramolecular structure of the microcompartment interior has been subject of study for some time and recent reports have provided molecular-level detail as to the forces governing internal lumen organisation and interaction networks (Blikstad et al, 2023;Flecken et al, 2020;Metskas et al, 2022;Ni et al, 2022Ni et al, , 2023Oltrogge et al, 2020Turnšek et al, 2023;Wang, Yan, et al, 2019). The intrinsically disordered proteins (IDPs) CsoS2 and CcmM in αand β-carboxysomes, respectively, are the primary Rubisco interaction partners (Oltrogge et al, 2020;Wang, Yan, et al, 2019;Zang et al, 2021).…”
Section: Carboxysome Biogenesismentioning
confidence: 99%